Luxury perceptions: luxury brand vs counterfeit for young US female consumers - Doss, Farrell; Robinson, Tammy (Journal of fashion marketing and management, 2013)
Purpose - The purpose of this study is twofold: expand the body of empirical knowledge of consumer luxury brand perceptions by using the Brand Luxury Index (BLI) scale to compare and contrast young female consumers' luxury perceptions for a luxury brand and counterfeits of that brand, and use the data from the research to investigate the psychometric properties of the BLI scale.Design methodology approach - A convenience sample of 215 female students across multiple programmes of study completed separate, modified BLI scales for the luxury brand and the counterfeits of that brand. The BLI scale taps five dimensions or factors of brand luxury using non-personal-oriented perceptions and personal-oriented perceptions.Findings - This study used a modified version of the original BLI scale. Results show that all rated perceptions of the luxury brand were significantly higher than those for the counterfeits of that brand. Between-subjects effects revealed that luxury perceptions of those whose last handbag acquisition was a luxury brand significantly differed from the luxury perceptions of those whose last handbag acquisition was a counterfeit brand. SEM results produced inadequate fit values for the luxury brand; but suggested adequate fit for the counterfeit of the luxury brand.Research limitations implications - As more luxury brand producers and retailers seek to expand their presence on the world arena, brand equity may be compromised by making luxury brands so ubiquitous in the market place. Reported perceptions in this research suggest the market may be saturated with luxury brands and that luxury brands may be "overexposed". Results from this study may only be applicable to young female college consumers. Also, since a particular luxury brand was used, results may not be generalized to other luxury brands. Additional research is needed that looks at other populations' perception of luxury brands.Originality value - No research has been found that compared young consumer luxury perceptions for both luxury brands and their counterfeits. An investigation of this area would provide additional insight on consumer perceptions for luxury and counterfeit brands.